Efeitos pré e pós sinápticos dos inibidores da acetilcolinesterase na neurotransmissão em musculatura lisa. - Pereira, Janaína Drawanz [UNIFESP] (2010)
Justification: The present work considers the effects of new inhibitors of acetylcholinesterase (AChE) on the reactivity and neurotransmission in rats and mice. The new anticholinesterase compounds, ITH12118 and ITH12117, have an hybrid stucture, derived from the molecule of of the anticholinesterase Tacrine and the 1,4 dihydropyridine nimodipine, a blocker of l-type calcium channel blocker. The objective of the syntesis was to obtain drugs as candidates for the theatment of Alzheimer’s disease. Material and Methods: Contraction experiments were initialy made to compare de actions of ITH12118 and ITH12117 with that of Physostigmine, Tacrine and Nimodipine in vas deferens of rats (RVD) and mice (MVD) on concentration-response curves (CRC) for ACh, for the measurement of the folowwing parameters: maximum effect (Emax), 50% effective dose (ED50), aparent affinity (pD2), dose ratio for agonist (DR) to evaluate the potentiation by cholinesterase blockers, intrinsic activity (a) of agonists and relative responsiveness () to evaluate the maximum effect of ACh receptor. For the study of the role of calcium, cumulative and time-response curves for this ion were made, in the presence of cholinesterase blockers and Nimodipine, besides the measurement of cytosolic calcium by means of fluorescent FURA-2AM. In addition, curves for transmural electrical stimulation were also made for the study of neurogenic contractions. CRC for NA were also made. Furthermore, the activity of the enzyme AchE was also analysed in microplates, in the presence of blockers. Finaly, tests after treatment in vivo were made for Physostigmine and tests for learning and memory of mice, after treatment with Tacrine and ITH12118. Results: After measuments of DR, we have observer a higher potentiation of the curves of ACh by Physostigmine, followed by Tacrine and ITH12118 in RVD, and a slght potentiation by Physostigmine and Tacrine in MVD. However, the Emax of the CRC for ACh was greatly decreased in the presence of anticholinesterase blockers in RVD and and in MVD after ITH12118 and ITH12117. The experiments with Ca2+ showed a significant block by Nimodipine and ITH12118 in RVD, and by ITH12117 in MVD. In relation to the contraction by electrical transmural stimulation, just a block of tonic contraction was induced by ITH12118. The experiments in microplates showed a block of AChH by Fisotigmine and Tacrine in RVD and MVD, and in rat and mouse in Central Nervous Sistem, with a blockade by higher concentrations of ITH12118 and ITH12117. In rat and mouse cortex ITH12118 and ITH12117 showed a higher potency of blockade. A higher proportion of BuChE was shown in RVD, and in preliminary contraction experiments with Iso-OMPA, a selective blocker of BuChE, and Physostigmine, showed that a reduction of Emax is lower in the presence of Physostigmine isolatedly. The curves for NA were blocked in RVD by Nimodipine and ITH12118 and by Nimodipine, ITH12118 and ITH12117 in MVD. After treatment in vivo, the curves for ACh were not displaced. The evaluation of learning and memory did not show significant differences from controls, but a tendency for a higher retention of memory was presented after Tacrine and ITH12117. Conclusions: The potentiation of ACh in the dosis axis is within the expectations for the block of cholinesterase by the antagonists. However, the decrease of Emax needs further investigation. According to the contraction experiments, compounds ITH12118 and ITH12117 showed a higher potency as blockers of calcium channels than of cholinesterase. The changes between RVD and MVD seem to be related to the higher concentration of BuChE in RVD, but this point needs additional investigation.